Estudo da máquina síncrona à ímã permanente, sob diferentes modos de operação e distintas filosofias de controle - Salvador Júnior, Nelson (1995)
The aim of this work is the analysis of the permanent magnet synchronous machine (PMSM) under various operational modes and control philosophies A complete mathematical modeling is developed which includes: salient poles, damping windings and excitation by field current. The foliowing operation modes are considered, for the permanent magnet synchronous machine: direct axes current equal to zero, unitary power factor and constant resultant flux. The three control philosophies considered are: hysteresis scalar controller, ramp-comparison scalar controller and space-vector controller. A factor Kv is defíned which indicates the necessary capacity of the inverter. It is also defíned a factor KM that indicates the permanent magnet demagnetization levei. The comparative analysis includes: the factors Kv and KM, the ripple and cogging torque, the ripple current, the power factor, the torque magnitude, the leveis of voltage and current and the step response time The work is useful in design of PMSM drives.